Do Consumers of Online Transportation Services Get Legal Protection? - Elfrida Ratnawati Gultom; Meta Indah Budhianti (Universitas Negeri Gorontalo, 2022)
Currently all the desired needs can be easily obtained, including the transportation of people or goods from one place to the destination. Only by downloading an online-based transportation application and pressing a button on a smartphone, the two- and four-wheeled transportation process can be carried out. Who is responsible in the event of an accident to passengers and damage to goods in the online-based transportation process? Do passengers and property owners get legal protection? is the subject matter that will be discussed in this article. The normative research method is used in this article, using secondary data and then processing it qualitatively by describing it descriptively. The conclusion obtained is the legal relationship between online vehicle drivers and the company as a liaison operator between the driver and passengers or the owner of the goods bound in a partnership agreement is responsible for consumer losses, this is written in the terms and conditions. Passengers and goods owners receive legal protection and compensation from online-based companies as operators due to accidents and damage to goods caused by online drivers.